2021
DOI: 10.1093/icesjms/fsab044
|View full text |Cite
|
Sign up to set email alerts
|

Mapping 3D structure of aSargassumforest with high-resolution sounding data obtained by multibeam echosounder

Abstract: Sargassum forests play an important role in coastal waters as habitats for marine organisms, including commercial species. However, human activities have negatively affected their distribution causing a worldwide decline of Sargassum forests. Mapping and monitoring the distribution and biomass of these habitats using acoustic remote sensing techniques is key for their conservation. Nonetheless, most researches based on acoustic remote sensing methods focus on estimations of macrophyte area and its canopy heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…To our knowledge, no studies have used multi-detect data for actual habitat mapping, although Schneider von Deimling et al (2007) used it for gas flaring detection. Hamana and Komatsu (2021) and Held and Schneider von Deimling (2019) used misclassifications of the bottom detection algorithm to identify benthic habitats in point cloud data (brown algae and seagrass, respectively). The target habitat of this study, the black coral forests formed by Anthipatella wollastoni (Gray, 1857) off the coast of Lanzarote, Spain, appears geometrically similar to a vegetated seabed, with corals protruding from the seabed a few decimetres into the water column (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no studies have used multi-detect data for actual habitat mapping, although Schneider von Deimling et al (2007) used it for gas flaring detection. Hamana and Komatsu (2021) and Held and Schneider von Deimling (2019) used misclassifications of the bottom detection algorithm to identify benthic habitats in point cloud data (brown algae and seagrass, respectively). The target habitat of this study, the black coral forests formed by Anthipatella wollastoni (Gray, 1857) off the coast of Lanzarote, Spain, appears geometrically similar to a vegetated seabed, with corals protruding from the seabed a few decimetres into the water column (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Controversially, the Acoustic method hardly to be affected by water turbidity, and it is possible to detect the target from a faraway area. There are previous studies that suggest a method to survey Sargassum distribution by Quantitative Echo Sounder (QES) (Minami et al 2012) and Multi Beam Echo Sounder (MBES) (Hamana and Komatsu, 2021). QES transmits the pulse downward and detects the target just below the sonar and cannot survey areas outside of the ship track.…”
Section: Introductionmentioning
confidence: 99%
“…The validation experiment of their system for plant growth monitoring will be performed in the future. Hamana et al [17] demonstrated that a multibeam echosounder can be used to map the 3D structure of a seaweed forest (both canopy height and inter-individual distances of the plants were measured).…”
Section: Introductionmentioning
confidence: 99%